54.7k views
21 votes
(2x+4)(x-1) express as a trinomial

User Ashanta
by
5.0k points

2 Answers

3 votes

Answer:


\huge\boxed{\bf{(2x + 4)(x - 1) = 2x^2 + 8x - 4}}

Explanation:


\sf \to (2x + 4)(x - 1)


\sf \to x(2x + 4) + 4(x - 1)


\sf \to 2x^2 + 4x + 4x - 4


\sf \to 2x^2 + 8x - 4


\:


\huge\colorbox{red}{BlackPain}

User Dan Healy
by
5.6k points
4 votes

Answer:


\\\\\hookrightarrow 2x^(2) +2x-4

Explanation:


\hookrightarrow (2x+4)(x-1) \\\\\hookrightarrow 2x(x-1)+4(x-1)\\\\\hookrightarrow 2x^(2) -2x+4x-4\\\\\hookrightarrow 2x^(2) +2x-4

User Lunny
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.